PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING UNTUK MEMBANTU MENINGKATKAN BERFIKIR KREATIF MAHASISWA - Triantoro, Miranu (Universitas Islam Balitar, 2022)
The research objective is to describe a project-based learning module that can help improve students' creative thinking. The module development uses Thiagarajan and Semmel 4D models, but only 3D is used, namely definition, design, and development. Dissemination is not carried out because it does not aim to generalize. The target of product trials for students of UNIPA Campus PPKn Blitar class 2018/2019. The data recording instruments used validation sheets, observation sheets, teaching materials mastery tests, and student response questionnaires. Data analysis used descriptive qualitative and descriptive statistical analysis. The results of the study (1) based on the criteria that have been set, all instruments meet the validity (2) the practicality of the module with the implementation aspect of the module reaches a score of 79.65% in the good category (3) lecturer activities in learning reach a score of 85.06% in the active category (4) Judging from the aspect of the effectiveness of the module with indicators of learning completeness reaching a score of 92.27% it is said to be complete, student activities reaching a score of 78.17% are in the active category. Student responses to the use of the module reached a score of 1.68% giving a positive response. The indicator states that this PBL module has met the valid, practical and effective requirements.